High Risk of Neutropenia in HIV-Infected Children following Treatment with Artesunate plus Amodiaquine for Uncomplicated Malaria in Uganda - Gasasira, Anne F.; Kamya, Moses R.; Achan, Jane; Mebrahtu, Tsedal; Kalyango, Joan N.; Ruel, Theodore; Charlebois, Edwin; Staedke, Sarah G.; Kekitiinwa, Adeodata; Rosenthal, Philip J.; Havlir, Diane; Dorsey, Grant (Clinical infectious diseases, 2008)
Artemisinin-based combination therapies are rapidly being adopted for the treatment of malaria in Africa; however, there are limited data on their safety and efficacy among human immunodeficiency virus (HIV)–infected populations. Methods. We compared malaria treatment outcomes between cohorts of HIV-infected and HIV-uninfected children in Uganda who were observed for 18 and 29 months, respectively. Malaria was treated with artesunate plus amodiaquine, and outcomes were assessed using standardized guidelines. HIV-infected children received trimethoprim-sulfamethoxazole prophylaxis and antiretroviral therapy in accordance with current guidelines. Results. Twenty-six HIV-infected participants experiencing 35 episodes of malaria and 134 HIV-uninfected children experiencing 258 episodes of malaria were included in the study. Twelve HIV-infected children were receiving antiretroviral therapy, 11 of whom were receiving zidovudine. Malaria treatment was highly efficacious in both the HIV-infected and HIV-uninfected cohorts (28-day risk of recrudescence, 0% and 3.6%, respectively); however, there was a trend towards increased risk of recurrent malaria among the HIV-uninfected children (2.9% vs. 13.2%; Pp.08). Importantly, the risk of neutropenia 14 days after initiation of treatment with artesunate plus amodiaquine was higher among HIV-infected children than among HIV-uninfected children (45% vs. 6%; P ! .001). The severity of all episodes of neutropenia in HIV-uninfected children was mild to moderate, and 16% of episodes of neutropenia in the HIV-infected cohort were severe or life-threatening (neutrophil count, !750 cells/ mm3). In the HIV-infected cohort, the risk of neutropenia was significantly higher among children who received antiretroviral therapy than among those who did not receive antiretroviral therapy (75% vs. 26%; Pp.001). Conclusions. Artesunate plus amodiaquine was highly efficacious for malaria treatment in HIV-infected children but was associated with a high risk of neutropenia, especially in the context of concurrent antiretroviral use. Our findings highlight an urgent need for evaluation of alternative antimalarial therapies for HIV-infected individuals.
Keywords: Neutropenia; HIV-Infected Children; Treatment; Artesunate plus Amodiaquine; Malaria; Uganda